2016
DOI: 10.1111/jai.13128
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of 50 mm T0 and T90 codends for commercial shrimp species in the Turkish deepwater trawl fishery, Eastern Mediterranean

Abstract: Summary The study compared the selectivity of 50 mm mesh size conventional (T0) and 90° turned mesh (T90) demersal trawl codends for four commercial shrimp species (Aristaeomorpha foliacea, Aristeus antennatus, Parapenaeus longirostris and Plesionika martia) in the Bay of Antalya in the eastern Mediterranean. Data were collected from 27 valid hauls using the covered codend method. Selectivity parameters were obtained using the logistic equation with the maximum likelihood method and by taking into account the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…T90 netting has interesting properties regarding species and size selection when used in codends. For instance, Deval et al (2016) tested codends with T90 meshes in four commercial shrimps of eastern Mediterranean trawl fisheries and showed that the percentage of escapes for all four species increases, as well as obtaining an increase in the L50. In Northern European fisheries, T90 codends have been subject to comprehensive studies that show a clear improvement in selectivity (Moderhak et al 1999) and in the quality of the fish marketed (Hansen 2004).…”
Section: Discussionmentioning
confidence: 99%
“…T90 netting has interesting properties regarding species and size selection when used in codends. For instance, Deval et al (2016) tested codends with T90 meshes in four commercial shrimps of eastern Mediterranean trawl fisheries and showed that the percentage of escapes for all four species increases, as well as obtaining an increase in the L50. In Northern European fisheries, T90 codends have been subject to comprehensive studies that show a clear improvement in selectivity (Moderhak et al 1999) and in the quality of the fish marketed (Hansen 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Damalas & Vassilopoulou, 2013;Bellido et al, 2014) and selectivity parameters still remain low for some species (e.g. Sala et al, 2008 and references therein;Deval et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the effect of mesh size on codend selectivity of brown shrimp is largely unknown and prevents the identification of optimal codend mesh size. In addition to mesh size, it has been demonstrated that altering codend mesh geometry using square mesh or T90 mesh (mesh orientation turned by 90°) can provide better selectivity for crustaceans than standard diamond-mesh codends [ 11 14 ]. Therefore, square-mesh codends or T90 codends may be alternative codend designs for the brown shrimp fishery.…”
Section: Introductionmentioning
confidence: 99%